Mading sebagai Minat Baca Siswa untuk Mengenal Integrasi Nasional dalam Bingkai Bhineka Tunggal Ika - Ronald D. Hukubun; Eva S. Ratuluhain; Novisty Mainake; Fatima Kubais; Siti S. Rumonin; Delce Kainama (Jurnal Pengabdian Kepada Masyarakat, 2024)
Learning activities carried out at Ambon 6 Public High School with the theme, namely Mading as Students' Interest in Reading to Get to Know National Integration in the Frame of Bhinneka Tunggal Ika. Where through this learning activity it is used with a cooperative learning model where students are given the opportunity to develop themselves through small groups with the aim of discussing in relation to the material on National Integration in the Frame of Unity in Diversity. Through these learning activities students develop knowledge and social skills in which there is an interaction relationship between teachers and students as well as students and students. Mading is the final result where all information relating to National Integration Within the Frame of Bhineka Tunggal Ika is poured or written on a picture, or there is a combination of the two. Inside the wall magazine is then presented in front of the class.